Astrocytes orchestrate neuroprotection and pathogenesis via bidirectional neuronal interactions in Parkinson’s disease - Yifan Li; Qiang Li; Yemin Wang; Xuejing Wang; Guangfu Di; Meng Niu; Zhiliang Xu; Yanjiao Huang (Journal of Physiology and Biochemistry, 2026)

Climatic predictors hierarchically regulate soil carbon components and microbial communities along an elevational gradient - Yuqian Li; Erwen Xu; Jiannan Lu; Xiurong Wu; Yicheng Zhang; Yuhan Fan; Enxian Zhou; Boyang Wang; Yuqiang Li; Xuyang Wang (Applied Soil Ecology, 2026)

Co-occurring Spirogyra sp. and enrofloxacin stressors interact to alter macrophyte interactions: evidence from a freshwater mesocosm experiment - Yuqing Tian; Cheng Lin; Xu Zhang; Hui Yang; Hongzhi Mao; Heyin Wang; Jiali Chen; Donghai Zhang; Jiangtao Hu; Xusheng Gong; Junyan Wu; Yuying Li; et al. (Aquatic Sciences, 2026)

Life cycle 3E (environmental–energy–economic) assessment of amine-based onboard carbon capture systems: optimal solvent screening for maritime decarbonization - Xiaojia Tang; Kehan Wang; Siyuan Xu; Shuyan Chen; Hanqiang Liu; Qingxin Wang; Can Zheng; Yangyuan Ji; Yimin Zhu (Clean Technologies and Environmental Policy, 2026)

Mechanisms of water-inrush mitigation under alternative grouting strategies during shaft sinking: Solidification-enabled stress–seepage–damage coupling - Wenxin Li; Dan Ma; Jiangyu Wu; Xuefeng Gao; Qiang Li; Changle Xu; Chuanjiu Zhang (Bulletin of Engineering Geology and the Environment, 2026)

Nonlinear Functional Connectivity and ICA Reveal Default Mode Network Hyperconnectivity in Parkinson’s Disease: A Resting-State fMRI Study - Charles Okanda Nyatega; Qiang Li; Weizhi Nie; Farhan Ahmad; Mohammed Jajere Adamu (Brain Topography, 2026)

Scientific analysis of hammerscales excavated from the Chengba and Guantian sites (‌50 BC to AD 400‌) in Southwest China - Chenxiaoxue Jia; Tianqiang Sun; Linheng Mo; Fuyao Tan; Hang Xiao; Qiang Li; Chenxi Liang; Yuming Xu; Jake Glover; Yuniu Li (Archaeological and Anthropological Sciences, 2026)

Beyond disinfection: innovative strategies for tackling resilient foodborne contaminants - Junyi Zhang; Jin Huang; Tongjiao Wu; Xueqiang Liu; Dandan Zhao; Jianxiong Hao (Critical Reviews in Food Science and Nutrition, 2026)

Dolomite characteristics and genetic mechanisms of Member 1, Sanya Formation in Well Xike 1, South China Sea - Chao Han; Yazeng Ma; Hong Xu; Zuozhen Han; Jinxiong Luo; Qiang Li; Yuetong Zhang (Journal of Oceanology and Limnology, 2026)

Corrigendum to “Organic fertilizer application enhances soil multifunctionality and yield of upland high-quality rice and reshapes potential microbial ecological networks” [Appl. Soil Ecol. 223 (2026) 107046] - Xiaqing Xu; Xiahong He; Yingfen Qin; Shu Wang; Jianqiang Li; Ping Xiang; Qiliang Yang; Yunfei Tuo (Applied Soil Ecology, 2026)

Long-term manure fertilization alters molecular composition of soil organic carbon in tobacco fields via microbial mediation - Xuebo Zheng; Xuelai Chen; Jiazhu Jiang; Haibin Li; Zengqiang Li; Wenjing Song; Jianxin Dong (Applied Soil Ecology, 2026)

Organic fertilizer application enhances soil multifunctionality and yield of upland high-quality rice and reshapes potential microbial ecological networks - Xiaqing Xu; Xiahong He; Yingfen Qin; Shu Wang; Jianqiang Li; Ping Xiang; Qiliang Yang; Yunfei Tuo (Applied Soil Ecology, 2026)

The Application of Herbal Medicines for Parasites Control in Aquaculture: A Review - Xiaoping Tan; Chengzhong Yang; Qianwen Zhou; Shenye Qu; Tianqiang Liu; Fei Ling; Gaoxue Wang (Reviews in Aquaculture, 2026)
With the ongoing expansion of intensive aquaculture, the emergence of parasite drug resistance and the increasing frequency of disease outbreaks have become significant challenges. Conventional antiparasitic agents are increasingly restricted due to burgeoning resistance, environmental persistence, and safety concerns. Consequently, the development of eco‐friendly and sustainable therapeutic alternatives has emerged as a primary research priority. Herbal medicines (HMs), characterized by a vast reservoir of structurally diverse and bioactive compounds, serve as ideal candidates for drug discovery in aquaculture. In recent years, substantial research effort has been directed toward identifying commercially viable HM‐derived agents for the fish farming industry. Advancements in isolation and purification technologies have facilitated the extraction of numerous insecticidal small molecules, while further studies have elucidated their underlying antiparasitic mechanisms. This review provides a comprehensive analysis of the role of HMs in preventing and treating aquatic parasitic infections, encompassing the isolation of active constituents, evaluation of efficacy, modes of action, and optimization of application strategies. Furthermore, we address the inherent challenges and future trajectories of utilizing HMs in aquaculture. By synthesizing current knowledge on these bioactive compounds, this review aims to facilitate the development of safe, highly bioavailable, and environmentally sustainable antiparasitic agents.

Vegetation restoration drives a shift from plant-derived to microbial-derived soil organic carbon accumulation in a semi-arid sandy land in China - Jiannan Lu; Yuqiang Li; Xuyang Wang; Chengzhuo Zheng; Jie Lian; Xueyong Zhao (Applied Soil Ecology, 2026)

Microbial traits mediate the functional components of soil organic carbon under long-term fertilization - Yanhong Yuan; Jiachang Zhang; Zhanrong Feng; Qi Zhang; Zihan Zhao; Qiang Li; Shuiqing Zhang; Gehong Wei; Xinhui Han; Minggang Xu; Andong Cai; Chengjie Ren (Applied Soil Ecology, 2026)

Carbon-Iron coupling drives the shift in nutrient and microbial processes via the iron gate mechanism in dryland paddy fields - Xinping Mao; Qiang Liu; Fang Wang; Nyumah Fallah; Fengpeng Han (Applied Soil Ecology, 2026)

Effects of co-application of microalgae and beneficial bacteria on flue-cured tobacco yield and soil microbial communities - Yu Peng; Yihua Quan; Wang Yao; Yi Zhao; Xinyao Liu; Deyuan Peng; Xiaoming Tang; Changwu Fu; Zhenhua Wang; Qiang Li (Applied Soil Ecology, 2026)

Estimation of secondary dune density in the hinterland of the Taklimakan Desert - Mingyu Wang; Huoqing Li; Yongqiang Liu (Aeolian Research, 2025)

A novel stress-sensitive permeability model for deformable porous media based on fractal geometry - Peng Xu; Chenhao Li; Zhiqiang Li; Shuxia Qiu; Mingxiu Zhan (Advances in Water Resources, 2025)

Migration mechanisms of oil-water-sand three-phase flow in unconsolidated sandstones during water flooding: An image analysis approach resilient to threshold interference - Maozhu Li; Yiqiang Li; Zhipeng Wang; Xinji Du; Lei Wang; Jinxin Cao; Zheyu Liu (Advances in Water Resources, 2025)

Microbial drivers of soil C:N:P stoichiometry dynamics during ecological restoration in sandy ecosystems - Xuyang Wang; Bo Yao; Hongling Yang; Xiaoming Mou; Yuqiang Li; Yulin Li (Applied Soil Ecology, 2025)

Long-term co-application of nitrogen and organic fertilizers enhances soil quality and wheat growth stability by modulating microbial communities - Qianyuan Duan; Qiang Liu; Ruizhe Yang; Xueqin Kong; Yuqi Gao; Shanchao Yue; Yufang Shen; Miaoping Xu (Applied Soil Ecology, 2025)

The interaction between mycorrhiza and phoD-harbouring bacteria influencing soil available phosphorus in Pinus massoniana plantations - Lifen Li; Yueming Liang; Qiang Li; Fujing Pan; Zhangqi Yang; Yanlan Wei; Yijing Li; Yanjun Chen; Hanlian Qin; Guangping Xu (Applied Soil Ecology, 2025)

Cover Image - Yuanliang Duan; Wenqiong Wu; Zhipeng Huang; Lu Zhang; Chengyan Mou; Zhongmeng Zhao; Han Zhao; Jun Du; Jian Zhou; Qiang Li (Reviews in Aquaculture, 2025)
The cover image is based on the article Research on Longsnout Catfish ( Leiocassis longirostris ) Worldwide: Current Status and Future Prospects by Qiang Li et al., https://doi.org/10.1111/raq.70092 . image

Research on Longsnout Catfish ( Leiocassis longirostris ) Worldwide: Current Status and Future Prospects - Yuanliang Duan; Wenqiong Wu; Zhipeng Huang; Lu Zhang; Chengyan Mou; Zhongmeng Zhao; Han Zhao; Jun Du; Jian Zhou; Qiang Li (Reviews in Aquaculture, 2025)
The longsnout catfish ( Leiocassis longirostris ) is primarily found in the Yangtze River Basin in China. This species has been studied for more than 40 years, predominantly by researchers at the Fisheries Research Institute, Sichuan Academy of Agricultural Sciences (Sichuan Fisheries Research Institute), Southwest University, and the Institute of Hydrobiology of the Chinese Academy of Sciences. Concurrently, multiple research institutions worldwide have also conducted studies on this species, including Aberystwyth University and the University of Copenhagen in Europe, the University of Hawaii and the University of Prince Edward Island in North America, Korea Maritime and Ocean University and the ICAR National Bureau of Fish Genetic Resources in Asia, and the University of Adelaide in Oceania. Most studies on L. longirostris have focused on aquaculture techniques. In this review, we consider all studies on L. longirostris from 1974 to 2023, providing a detailed analysis of the current research status regarding its aquaculture, physiological characteristics, germplasm resources, new variety development, and deep processing. We also speculated on potential future research directions. In summary, this review establishes a solid foundation for future scientific research and aquaculture production of the species, which may promote the further development of new varieties and value‐added products derived from L. longirostris .

Fertilization type affects the genetic potential for phosphorus mineralization but not for phosphorus solubilization at the continental scale - Yanhong Yuan; María Belén Barquero; Yu Li; Shuiqing Zhang; Hongzhu Fan; Huimin Zhang; Qiang Li; Shutang Liu; Linlin Shi; Andong Cai; Chengjie Ren; Minggang Xu; et al. (Applied Soil Ecology, 2025)

Ectomycorrhizal fungi explain more variation in rhizosphere nutrient availability than root traits in temperate forests - Xiaolei Yan; Lingyan Zhou; Yamin Chen; Ruiqiang Liu; Liqi Guo; Nan Li; Ao Kang; Kaiyan Zhai; Guiyao Zhou; Xuhui Zhou (Applied Soil Ecology, 2025)

Dynamics and resilience of earthworm fecal microbiomes under distinct feeding regimes - Ziyan Pan; Petr Heděnec; Qiang Lin; Lingjuan Li; Amirah Alias; Fang Deng; Jan Frouz (Applied Soil Ecology, 2025)

Effect of grafted scion varieties on apple root growth, carbon and nitrogen metabolism and microbiome in roots and rhizosphere soil - Huanhuan Zhang; Dongdong Yao; Guangxin Zhang; Hossam Salah Mahmoud Ali; Xujiao Li; Yanshu Li; Tianqiang Liang; Fengyun Zhao; Songlin Yu; Kun Yu (Applied Soil Ecology, 2025)

Soil Fusarium graminearum is inhibited by combined application of crop residues and an organic stimulant - Yunpeng Zhou; Tantan Zhou; Zengqiang Li; Qingxia Wang; Jisheng Xu; Dandan Li; Wei Guo; Bingzi Zhao (Applied Soil Ecology, 2024)

A new fractal pore-throat chain model for non-Darcy flow through porous media - Peng Xu; Zhiqiang Li; Jinqing Wang; Qing Chen; Shuxia Qiu (Advances in Water Resources, 2024)

Effects of sediment-borne nutrient and litter quality on macrophyte decomposition and nutrient release - Miao Wang; Tao Hao; Xuwei Deng; Zhengxiang Wang; Zhaohui Cai; Zhongqiang Li (Hydrobiologia, 2017)